The origins of Christianity : a historical introduction to the New Testament - Brown, Schuyler (Oxford Bible series., 1993)
This is a revised and updated version of a student textbook concerning the historical problems involved in the study of the New Testament and modern techniques for solving them. The author also examines the influence of the New Testament on subsequent religious and secular history.